Bi(OTf)3-catalysed intramolecular cyclisation of unsaturated acetals. Issue 34 (14th June 2021) - Saget, Raphaël; Jaunky, Piotr; Duñach, Elisabet
Abstract : A series of highly functionalized carbocycles was efficiently prepared via the selective cyclisation of unsaturated acetals and ketals in the presence of only 1 mol% of Bi(iii ) or Fe(iii ) triflates as the catalysts at room temperature, with yields ranging from 60 to 90%. Abstract : A series of highly functionalized carbocycles was efficiently prepared via the selective cyclisation of unsaturated acetals and ketals in the presence of only 1 mol% of Bi(iii ) or Fe(iii ) triflates as the catalysts at room temperature, with yields ranging from 60 to 90%. With Bi(OTf)3 catalysis, α, β-unsaturated ether carbocycles are formed selectively, whereas with the Fe(OTf)3 system, a cycloisomerisation to carbocyclic diethers is mainly obtained. This acetal/olefin cyclisation could be run at a multi-gram scale and compound 2c could be obtained on a 300 gram-scale with a yield of 69% after precipitation in hexane.